Traceability based description of clinical processes: Extension of IHE guidelines for phlebotomy workflows - Sulis, Alessandro; Frexia, Francesca; Meloni, Vittorio; Gaggero, Massimo; Del Rio, Mauro; Triunfo, Riccardo; Ghironi, Daniela; Caboni, Federico; Zanetti, Gianluigi (European Journal for Biomedical Informatics, 2016)
The increasing diffusion of data acquisition systems paves the way to traceability based process management and definition. In the clinical context, IHE formalizes the reference guidelines, periodically enhanced to reflect processes evolution. In this work we describe how we have modeled the phlebotomy process following the IHE references and best-practices to obtain a fully traceable workflow. The work has resulted in two new transactions for the IHE LBL profile, describing samples containers production and samples collection. The complete workflow has been implemented and successfully tested in real clinical environments. The traceability data acquired have then been studied using Process Mining techniques to compare the production model with idealized workflow and guide further developments.
Keywords: Phlebotomy; Clinical Laboratory Techniques; Quality Control; nemocniční informační systémy; data mining; řízení kvality; počítačové systémy; průběh práce; Computer Simulation; Workflow; sběr dat; Computer Systems; Hospital Information Systems; algoritmy; navrhování softwaru; zajištění kvality zdravotní péče; organizační modely; Software Design; klinické laboratorní techniky; Data Collection; Data Mining; Models, Organizational; Algorithms; flebotomie; počítačová simulace; Quality Assurance, Health Care; Diagnostic Errors; laboratoře; Laboratories; chybná diagnóza